Identification of an infectious progenitor for the multiple-copy HERV-K human endogenous retroelements - Dewannieux, Marie; Harper, Francis; Richaud, Aurélien; Letzelter, Claire; Ribet, David; Pierron, Gérard; Heidmann, Thierry (Genome Research, 2006)
Human Endogenous Retroviruses are expected to be the remnants of ancestral infections of primates by active retroviruses that have thereafter been transmitted in a Mendelian fashion. Here, we derived in silico the sequence of the putative ancestral “progenitor” element of one of the most recently amplified family—the HERV-K family—and constructed it. This element, Phoenix, produces viral particles that disclose all of the structural and functional properties of a bona-fide retrovirus, can infect mammalian, including human, cells, and integrate with the exact signature of the presently found endogenous HERV-K progeny. We also show that this element amplifies via an extracellular pathway involving reinfection, at variance with the non-LTR-retrotransposons (LINEs, SINEs) or LTR-retrotransposons, thus recapitulating ex vivo the molecular events responsible for its dissemination in the host genomes. We also show that in vitro recombinations among present-day human HERV-K (also known as ERVK) loci can similarly generate functional HERV-K elements, indicating that human cells still have the potential to produce infectious retroviruses.